Teaching strategies based on multiple intelligences theory among science and mathematics secondary school teachers - Sulaiman, Tajularipin; Abdurahman, Abdul Raub; Abdul Rahim, Suzieleez Syrene (Elsevier, 2010)
Instructions in science and mathematics required various teaching strategies to ensure successful teaching and learning process. Science and mathematics teachers can optimize the effect of teaching when they realized the strengths of multiple intelligences they posses and how they can apply them in their teaching. Thus, the primary objectives of this study are to investigate: 1) the multiple intelligences profile of science and mathematics secondary school teachers 2) the teaching strategies based on multiple intelligences that are applied by science and mathematics teachers and 3) the relationship between multiple intelligences profile of science and mathematics teachers with the teaching strategies based on multiple intelligences applied in the classroom. 174 respondents were chosen randomly from various secondary schools in peninsular Malaysia. Questionnaires were used to investigate the level of multiple intelligences and teaching strategies. Correlation analysis was applied to investigate the relationship between multiple intelligences and teaching strategies. Teaching strategies based on multiple intelligences suggest teaching science and mathematics in multiple ways. Teachers’ profiles of multiple intelligences assist them to obtain a better understanding of their potential intelligences and interests in enhancing their teaching strategies.